2010
DOI: 10.1002/acp.1645
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of video and static photo lineups with child and adolescent witnesses

Abstract: In the UK video parades are the preferred method of identification employed in criminal cases. This policy implementation has been employed with little or no evidence concerning its validity. The reported research examines the effect of new video technology on children's identification evidence. The study compared 7-9 and 13-15-year olds' ability to make identifications from either video or static photo lineups. Two hundred and fifteen participants witnessed a live event and then after a delay of 2-3 days view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 45 publications
(83 reference statements)
2
29
0
Order By: Relevance
“…In the present study, older children may have been more able than younger children to effectively use the additional information provided by the moving images to improve their performance to adult-like levels (see Havard, Memon, Clifford, & Gabbert, 2010). While nothing can be done necessarily to help children better encode the perpetrator, further research studies employing ROC analyses could establish whether there are procedural variations in the administration of lineups that significantly enhance younger children's ability to discriminate the target from the fillers (for a review of lineup identification procedures see Pozzulo, 2007;Pozzulo & Lindsay, 1998).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the present study, older children may have been more able than younger children to effectively use the additional information provided by the moving images to improve their performance to adult-like levels (see Havard, Memon, Clifford, & Gabbert, 2010). While nothing can be done necessarily to help children better encode the perpetrator, further research studies employing ROC analyses could establish whether there are procedural variations in the administration of lineups that significantly enhance younger children's ability to discriminate the target from the fillers (for a review of lineup identification procedures see Pozzulo, 2007;Pozzulo & Lindsay, 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Employing moving as opposed to static photographic lineups is the recommended practice for lineups conducted in the UK, in Australia and in some jurisdictions in the US. Research examining the effects of movement on children's (Beresford & Blades, 2006;Havard, et al, 2010) and adult's (Cutler & Fisher, 1990;Darling, Valentine, & Memon, 2008;Valentine, Darling, & Memon, 2007) identification performance has produced mixed results. In the present study, it is possible that viewing moving faces may have provided children and adults with additional information that may have enhanced memory retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Beresford and Blades (2006) found no differences in correct identifications for 6Á7 year olds and 9Á10 year olds. Havard, Memon, Clifford, and Gabbert (2010) found no differences in correct identifications for children aged 7Á9 years of age and adolescents aged 13Á15 years and Havard and Memon (2013) found no differences in correct identifications for children aged 5Á7 and 8Á11 years of age.…”
mentioning
confidence: 83%
“…When it comes to correctly rejecting a TA lineup, that is, correctly stating the 'person is not there', the majority of eyewitness research reports that children are significantly more likely than adults to falsely identify someone from a lineup (Dekle, Beal, & Honeycutt, 1996;Humphries et al, 2012;Lindsay et al, 1997;Parker & Ryan, 1993;Pozzulo & Balfour, 2006;Pozzulo & Warren, 2003, Expt 1, see Table 1). Although there are a couple of studies that have found that older children aged 12Á14 years can perform like adults on TA lineups Pozzulo & Warren, 2003, Expt 2), or more accurately than younger children (Havard et al, 2010), it has not been consistently confirmed at what age older children and adolescents behave like adults with TA lineups.…”
mentioning
confidence: 99%
“…Half of the lineups were target present (TP) and half target absent (TA), and half contained the 'mystery man' and half did not. The lineups were created by an experienced VIPER operator, in the same manner as a real identification parade, and foils were chosen from the VIPER database using the same procedure as reported by Havard, Memon, Clifford and Gabbert (2010) and Valentine, Darling and Memon (2007). The VIPER database was searched by entering keywords of the suspect's description (e.g.…”
Section: Methodsmentioning
confidence: 99%